Optimation PAN/TiO2 Nanofiber Membrane as Separator for Symmetric Supercapacitor - Nasikhudin, Nasikhudin; Agustina, Silvia Nurlaili; Diantoro, Markus; Yogihati, Chusnana Insjaf; Suryana, Risa; Alias, Yatimah Binti (Journal of Engineering and Technological Sciences, 2025)
Supercapacitor is one of the energy storage systems known for their high-power density, long cycle life, and good cycling stability. To improve supercapacitor performance, we used a polymer PAN composite titanium dioxide (TiO2) as the separator material. Nanofiber separator membranes of PAN/TiO₂ with various masses (0, 5, 10, 15, and 20 wt%) were successfully synthesized using the electrospinning technique. The addition of TiO2 for modified fiber, due to its high absorption rate for energy storage, increased electrolyte uptake and optimized supercapacitor performance. The morphology, functional groups, crystallinity, and thermal stability of the membranes were identified using scanning electron microscope (SEM), Fourier transform infra-red (FTIR), x-ray diffraction (XRD), and thermogravimetric analysis (TGA), respectively. It was found that the membrane with 15 wt% TiO2 exhibited a fiber diameter of 224.73 nm, pore size of 138.98 nm, the highest porosity of 66.50%, electrolyte uptake of 240%, and thermal stability up to 282°C, with a remaining mass of 3.94% after being tested at 1000°C. The electrochemical performance of the supercapacitors was measured using galvanostatic charge-discharge (GCD), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). The membrane containing 15 wt% TiO2 demonstrated optimum ionic conductivity of 4.4 x 10-4 S/cm, gravimetric capacitance of 57.770 F. g-1, and capacitance retention of 94.22% after 1000 test cycles.